2018
DOI: 10.3904/kjim.2016.140
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between NADPH oxidase-mediated oxidative stress and dysfunction of endothelial progenitor cell in hyperlipidemic patients

Abstract: Background/AimsNADPH (nicotinamide adenine dinucleotide phosphate) oxidase (NOX)-mediated oxidative stress plays a key role in promotion of oxidative injury in the cardiovascular system. The aim of this study is to evaluate the status of NOX in endothelial progenitor cells (EPCs) of hyperlipidemic patients and to assess the correlation between NOX activity and the functions EPCs.MethodsA total of 30 hyperlipidemic patients were enrolled for this study and 30 age-matched volunteers with normal level of plasma l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Lipid toxicity is an important cause of metabolic cardiomyopathy in rodents and humans ( Li et al, 2018 ). Hypertriglyceridemia causes abnormalities in the intake and circulating levels of FFA as well as abnormal degrees of oxidation ( Li et al, 2018 ), ultimately inducing pathological changes, such as myocardial cell apoptosis ( Yang et al, 2014 ). Many studies have suggested that cardiomyocyte apoptosis is closely related to impaired myocardial function.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid toxicity is an important cause of metabolic cardiomyopathy in rodents and humans ( Li et al, 2018 ). Hypertriglyceridemia causes abnormalities in the intake and circulating levels of FFA as well as abnormal degrees of oxidation ( Li et al, 2018 ), ultimately inducing pathological changes, such as myocardial cell apoptosis ( Yang et al, 2014 ). Many studies have suggested that cardiomyocyte apoptosis is closely related to impaired myocardial function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study involved only a small number of people (30 hyperlipidemic patients and 30 age-matched volunteers), the results showed an increase in NOX expression (NOX2 and NOX4), NOX activity, and consequently ROS production in hyperlipidemic patients, leading to a reduction in EPC functions. This positive correlation between the NOX-mediated oxidative stress and the dysfunctions of circulating EPCs in hyperlipidemic patients suggests that the inhibition and/or downregulation of NOX might be useful as novel strategy to improve EPC functions in hyperlipidemia [ 164 ]. The same research group previously obtained similar results in a rat model [ 165 ].…”
Section: Noxs In Endothelial Progenitors: Effect On Cell Survival Proliferation and Angiogenic Functionmentioning
confidence: 99%
“…NOX4-derived ROS production has been implicated in endothelial dysfunction and inflammation during obesity [167,168]. Evidence has shown that miR-25 is expressed in ECs [169].…”
Section: Oxidative Stress and Mirnasmentioning
confidence: 99%